2010
DOI: 10.1177/0271121410364250
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Family-Systems Intervention Practices on Parent-Child Interactions and Child Development

Abstract: The manner in which family-systems intervention practices were related to both parent-child interactions and child development was the focus of the meta-analysis described in this paper. The family-systems model that was investigated has been developed and updated during the past 25 years (Dunst, Trivette, & Deal, 1988;Trivette, Deal, & Dunst, 1986). Each version of the model includes key elements from social systems (Bronfenbrenner, 1979), empowerment (Rappaport, 1981, family strengths (Stinnett & DeFrain, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
192
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(208 citation statements)
references
References 67 publications
10
192
0
6
Order By: Relevance
“…Thus, the relationships between the level of needs, parental self-efficacy, and perceived control over services indicate that services need to be provided in a manner that strengthens parental self-efficacy and control over services. This interpretation of the results is supported by meta-analytic structural equation model studies that show that when professionals work in a capacity-building manner, parents self-efficacy is strengthened, and parental and child well-being increases (Dunst and Trivette 2009;Trivette, Dunst, and Hamby 2010). Further support for this interpretation is provided by the strong statistical relationship in this study between parent's perceived control over services and their satisfaction with the specific support provided to their child.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, the relationships between the level of needs, parental self-efficacy, and perceived control over services indicate that services need to be provided in a manner that strengthens parental self-efficacy and control over services. This interpretation of the results is supported by meta-analytic structural equation model studies that show that when professionals work in a capacity-building manner, parents self-efficacy is strengthened, and parental and child well-being increases (Dunst and Trivette 2009;Trivette, Dunst, and Hamby 2010). Further support for this interpretation is provided by the strong statistical relationship in this study between parent's perceived control over services and their satisfaction with the specific support provided to their child.…”
Section: Discussionsupporting
confidence: 70%
“…When parents report good self-efficacy, it affects how they feel as parents, how worried they are, and their relationship with their child (Dempsey and Dunst 2004;Wakimizu et al 2011). Studies have also shown that supporting self-efficacy will have an effect on parental and child well-being and that parents with a high self-rated selfefficacy rate their needs for support lower (Trivette, Dunst, and Hamby 2010). Whether these patterns hold true in Sweden is unknown, but it is likely that parents with higher self-efficacy have lower perceived needs for support and information.…”
Section: Introductionmentioning
confidence: 99%
“…Trivettte and Dunst (2000) and Trivette, Dunst and Humby (2010) identified seventeen evidence-based family-centered practices and grouped them into four categories: (1) Families and professionals share responsibilities and work collaboratively in order to share expert knowledge so that families can make informed decisions; (2) practices strengthen the family's functioning as supports allow families to take advantage of not only formal but informal supports to lead the life that they want; (3) practices are flexible and adjusted to the needs, values, and beliefs of the families; and (4) practices mobilize the strengths of the families in order to take advantage of their daily routines. Trivette et al (2010) stated that results show that FCM practices aimed at promoting parental competences (empowerment) have a direct effect on the parents' beliefs about their self-efficacy and well-being; and indirect effects on the improvement of the parents' interactions with their child, generating as a result more and better opportunities for their development. In this same respect, Trivette and Dunst (2009) observed that the family-centered approach, rather than the professional-centered approach, helps parents to be more capable and competent to promote their child's development as it improves the family functioning, promotes some specific competences, confidence in their possibilities and their satisfaction.…”
Section: Final Considerationsmentioning
confidence: 99%
“…It also ties in with the current emphasis in the field of disability on applying a family-centered approach (McWilliam 2012) which identifies and stresses the strengths and capabilities (Trivette and Dunst 2013;Trivette et al 2010) of families to promote positive family functioning. For Guralnick (2011), supporting families in their caregiving role by designing interventions based on their strengths is likely to bring important benefits.…”
Section: Introductionmentioning
confidence: 98%